Sézary syndrome: old enigmas, new targets - Nicolay, Jan Peter; Felcht, Moritz; Schledzewski, Kai; Goerdt, Sergij; Géraud, Cyrill (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Sézary syndrome, the leukemic variant of cutaneous T-cell lymphoma, is still an enigmatic disease with a fatal prognosis. Recent research, however, has identified a multitude of dysregulated molecular pathways that contribute to malignant transformation and therapy resistance of Sézary cells (SC). With respect to T-cell development, SC either represent naive T cells, T effector memory or T central memory cells. Functionally, SC may differentiate into Th2, Treg, or even Th17 cells. Despite their plasticity, SC express characteristic diagnostic marker proteins including CD158k, CD164, FcRL3, and PD-1 as well as skin-homing receptors such as CLA and CCR4. Already tested in (pre)clinical trials, CD158k, PD-1, CTLA-4, and CCR4 also represent promising therapeutic targets. Molecular alterations in SC include transcription factors such as STAT3, 4, and 5, as well as TWIST1 and TOX. TWIST1 induces expression of DNM3os containing the miR-199a2/214 cluster, a key hub controlling multiple cancer networks. In addition, activation of NFκB and the MAPK pathway as well as altered TCR signaling cause apoptosis resistance. Recently, whole genome and exome sequencing has revealed somatic copy number variations as predominant mutations in SC, primarily affecting apoptosis, NFκB signaling, DNA integrity, and T-cell activation. In order to facilitate development of novel therapies, improved in vivo models, which better reflect the pathogenesis and clinical course of Sézary syndrome, are currently being generated.